Enhancing Inventory Accuracy through Structured Stock Opname in Semi Digital Warehousing: A Case Study from PT. Sumber Alfaria Trijaya, Central Sulawesi - Zaenal; Bakri, Suardi (Yayasan Sinergi Kawula Muda, 2025)
This study investigates the implementation and impact of structured stock opname practices on inventory accuracy within a semi digitized retail warehouse environment in Indonesia. Conducted at PT Sumber Alfaria Trijaya’s warehouse in Palu, the research aims to assess how periodic physical inventory verification, supported by barcode technology and revised SOPs, contributes to reducing stock discrepancies and enhancing operational performance. Using a qualitative case study approach, the study involved semi structured interviews, on site observations, and document analysis over a five year period (2019–2023). Findings reveal that the consistent execution of stock opname, supported by hybrid inventory systems, led to a decline in discrepancy rates from 2.13% in 2022 to 1.66% in 2023 despite increasing inventory volumes. Improvements in warehouse layout, employee training, and the adoption of barcode scanners contributed to more efficient inventory reconciliation and data synchronization. The research demonstrates that even partial digitization, when strategically implemented, can significantly enhance supply chain reliability in resource constrained settings. The results contribute to academic and practical discourse by offering insights into adaptive warehouse practices in developing economies and underscore the role of structured procedures and technological integration in modern inventory control systems.